(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The general presumption is that the value of similar items in similar conditions is equal and doesn’t affect by the gender. But price differs for similar items such as cosmetics, beauty products etc. Even for the insurance companies it is different and they see gender an important parameter not only in the life insurance, motor/auto insurance, health insurance and other line of insurance.